Efficacy of AST-120 for Patients With Chronic Kidney Disease: A Network Meta-Analysis of Randomized Controlled Trials - Su, Pei-Yu; Lee, Ya-Han; Kuo, Li-Na; Chen, Yen-Cheng; Chen, Chiehfeng; Kang, Yi-No; Chang, Elizabeth H. (Frontiers in Pharmacology, 2021)
AST-120, an oral spherical activated carbon, may delay the need for kidney dialysis and improve uremia symptoms because it can adsorb acidic and basic organic compounds, especially small-molecule uremic toxins. However, previous studies produced no conclusive evidence regarding the benefits of AST-120 in delaying the progression of chronic kidney disease (CKD). Therefore, this systematic review and network meta-analysis evaluated the effects of AST-120 in patients with CKD. Related keywords of CKD and AST-120 were used to search four databases to obtain potential evidence on this topic, and two authors individually completed evidence selection, data extraction, and quality assessment. Network meta-analysis was performed for mortality, end-stage renal disease, composite renal outcomes, and laboratory outcomes based on a frequentist approach. In total, 15 randomized controlled trials (n = 3763) were included in the present synthesis, and the pooled results revealed non-significant differences in mortality among the treatment strategies. Low- and high-dose AST-120 were not superior to no AST-120 treatment regarding renal outcomes. However, the event rates of end-stage renal disease (risk ratio [RR] = 0.78, 95% confidence interval [CI] = 0.62–0.99) and composite renal outcomes (RR = 0.78, 95% CI: 0.63–0.97) were significantly lower in the tailored-dose AST-120 group than in no AST-120 group. The results did not reveal a small-study effect on the outcomes. Tailored dosing of AST-120 appeared to represent an optimal treatment strategy because it resulted in lower rates of composite renal outcomes and end-stage renal disease.